Evaluasi Learning Management System Timedoor Academy Pro dengan Metode Usability Testing - Athazaina, Naudy Taj; Paramitha, A.A. Istri Ita; Purnama, I Nyoman (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The internet development has advanced the education sector in Indonesia, encouraging the use of Learning Management Systems (LMS) for distance learning. Timedoor Academy Pro is one of the EduTech companies that uses LMS, but the LMS has never been tested on users and often confuses users. Therefore, a usability evaluation was conducted using Performance Measurement, Retrospective Think Aloud, and System Usability Scale (SUS) techniques to identify usability problems and evaluate system quality. Respondents were categorized into mentor users and students into advanced and beginner respondents. The evaluation results showed that the Timedoor Academy Pro LMS was not effective as seen from errors when respondents worked on task scenarios, and was not efficient as seen from differences in task completion time from the Mann-Whitney statistical test, and users were dissatisfied with the SUS score of 52 for mentors and 46 for students. Recommendations for improvement include changing the page layout, navigation menu, minimizing task steps, and adding features according to HCI guidelines and respondent suggestions.Kata kunci: Usability Testing; Learning Management System; Performance Measurement; Retrospective Think Aloud; System Usability Scale AbstrakPerkembangan internet memajukan sektor pendidikan di Indonesia, mendorong penggunaan Learning Management System (LMS) untuk pembelajaran jarak jauh. Timedoor Academy Pro menjadi salah satu perusahaan EduTech yang menggunakan LMS, namun LMS tersebut belum pernah diuji kepada pengguna dan sering membuat bingung pengguna. Sehingga, dilakukan evaluasi usability menggunakan teknik Performance Measurement, Retrospective Think Aloud, dan System Usability Scale (SUS) untuk mengidentifikasi masalah usability dan mengevaluasi kualitas sistem. Responden dikategorikan menjadi pengguna mentor dan siswa yang dikelompokkan menjadi responden mahir dan pemula. Hasil evaluasi menunjukkan bahwa LMS Timedoor Academy Pro belum efektif dilihat dari terdapat kesalahan saat responden mengerjakan task scenario, dan belum efisien dilihat dari terdapat perbedaan waktu pengerjaan task scenario dari pengujian statistik mann-whitney, serta pengguna merasa kurang puas dengan skor SUS 52 untuk mentor dan 46 untuk siswa. Rekomendasi perbaikan meliputi perubahan tata letak halaman, menu navigasi, meminimalisir langkah tugas, dan penambahan fitur sesuai panduan HCI dan saran responden.